Seedling Emergence and Early Growth of Maireana Brevifolia as Affected by Seed Treatment - Bennett, T.; Collins, D.; Pritchard, Deborah (Australian Instititue of Agricultural Science and Technology, 2014)
Small leaf bluebush (Maireana brevifolia) is an Australian native halophyte of potential value in agricultural systems, given its ability to grow and persist on sites negatively affected by soil constraints, such as salinity. Its adoption in farming systems is limited because seed germination and establishment is poorly understood. This study investigated the effect of three seed treatments; oven drying, cool storage and gibberellic acid on seedling emergence and early growth of Maireana brevifolia. The emergence of Maireana brevifolia was not improved by any combination measured by x-ray ranged from 49% - 64% with an average of 54.7 ± 1.42% (n = 10), indicating that germination Seed treatments did not increase seedling growth of Maireana brevifolia. Further research is required to better understand the factors affecting Maireana brevifolia seed viability to improve the adoption of large scale plantings on unproductive agricultural land.